2021
DOI: 10.1186/s13756-021-01013-7
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of ESBL-producing Escherichia coli from repeated prevalence studies over 11 years in a long-term-care facility

Abstract: Background Escherichia coli sequence type (ST) 131 H30 is an emerging multidrug resistant subclone, known to spread and cause outbreaks in long-term care facilities (LTCFs). Objectives and methods From 2010 through 2020, we performed 11 yearly surveillance studies for determining the prevalence of digestive carriage of ESBL-producing E. coli (ESBL-EC) among residents in a university-affiliated LCTF. Sequencing and genotyping of selected isolates we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…People residing in chronic care facilities are at increased risk of gut colonization with MDROs, but the estimated prevalence varies between countries [71,72]. For instance, in Switzerland (2010-2020), 10.5% of the long-term care facilities (LTCF) residents were colonized with ESBL-Ec, of which 58% belonged to the pandemic sequence type (ST) 131 lineage [73]. Consistent results were obtained in a more recent national Swiss study (2019), with an ESBL-Ent carriage of 11.6% and again a high prevalence of ST131 Ec strains [74].…”
Section: Long-term Care Facilities and Nursing Homesmentioning
confidence: 99%
“…People residing in chronic care facilities are at increased risk of gut colonization with MDROs, but the estimated prevalence varies between countries [71,72]. For instance, in Switzerland (2010-2020), 10.5% of the long-term care facilities (LTCF) residents were colonized with ESBL-Ec, of which 58% belonged to the pandemic sequence type (ST) 131 lineage [73]. Consistent results were obtained in a more recent national Swiss study (2019), with an ESBL-Ent carriage of 11.6% and again a high prevalence of ST131 Ec strains [74].…”
Section: Long-term Care Facilities and Nursing Homesmentioning
confidence: 99%
“…This review also demonstrated that most of the studies reported a decline in the prevalence of ESBL-producing E. coli and ESBL-producing K. pneumoniae during COVID-19 pandemic. This is in contrast to the rising trend of ESBL-producing Enterobacteriaceae infections prior to the COVID-19 pandemic [62] , [63] . This implies that there was a reduction in the prevalence of ESBL-producing Enterobacteriaceae during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 58%
“…According to data from Asia, Latin America, Europe, and Africa, the dramatic increase in third-generation cephalosporin resistance in Enterobacteriaceae is mainly due to the spread of bla-CTXM-15 ESBL (3)(4)(5),with bla CTXM-15 being the most common ESBL gene worldwide (6,7). While most studies of MDR ESBL-producing Enterobacteriaceae have focused on Escherichia coli (8)(9)(10)(11)(12)(13)(14)(15), few studies have characterized the whole genome of MDR ESBL-producing Klebsiella pneumoniae, even though this agent is one of the most widespread MDR ESBL-producing Enterobacteriaceae associated with extra-intestinal infections both in hospital and community settings (16)(17)(18)(19)(20)(21). Moreover, several strains of K. pneumoniae have been linked to multinational epidemics all over the world (21,22).…”
Section: Introductionmentioning
confidence: 99%